EMF : Eclipse Modeling Framework - Steinberg, Dave (Eclipse series., 2008)
"The Eclipse Modeling Framework enables developers to rapidly construct robust applications based on surprisingly simple models. Now, in this thoroughly revised Second Edition, the project's developers offer expert guidance, insight, and examples for solving real-world problems with EMF, accelerating development processes, and improving software quality." "This edition contains more than 40% new material, plus updates throughout to make it even more useful and practical. The authors illuminate the key concepts and techniques of EMF modeling, analyze EMF's most important framework classes and generator patterns, guide you through choosing optimal designs, and introduce powerful framework customizations and programming techniques."--Jacket